2020
DOI: 10.14198/jhse.2021.161.08
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, stress and burnout among basketball referees

Abstract: The study analyses leadership styles and their influence on burnout and stress among basketball referees, applying a non-probabilistic sampling, convenience sampling, to 61 referees, 85.2% men, 14.8% women. Descriptive analysis, correlations and hierarchical multiple regression models were performed. By applying the Multifactor Leadership Questionnaire MLQ-5, Inventario de Burnout en deportistas Revisado IBD-R [Revised Athlete Burnout Inventory], and Escala de Estrés en el Ámbito Deportivo EEAD [Stress Scale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…To this problem of a lack of research, we must add the particular case of the grassroots football referee [33], numerous and out of the media spotlight, since the few studies, but with increasing attention, focus mainly on the case of the major professional leagues [34][35][36]. In this area, a burnout prevalence rate of 2.44% was identified among the collective, with a higher trend among the main referees of the Spanish First Division and with more experience, also finding some relationship between burnout, stress, anxiety and social support, already observed in previous works [18,37,38].…”
Section: Theorical Background and Hypothesismentioning
confidence: 59%
See 2 more Smart Citations
“…To this problem of a lack of research, we must add the particular case of the grassroots football referee [33], numerous and out of the media spotlight, since the few studies, but with increasing attention, focus mainly on the case of the major professional leagues [34][35][36]. In this area, a burnout prevalence rate of 2.44% was identified among the collective, with a higher trend among the main referees of the Spanish First Division and with more experience, also finding some relationship between burnout, stress, anxiety and social support, already observed in previous works [18,37,38].…”
Section: Theorical Background and Hypothesismentioning
confidence: 59%
“…These variables were added in accordance to a study done together with experts, indicated in the methodology, in order to determine and empirically prove whether the environment and physical or verbal aggression influence professional effectiveness, as reflected in the list of internal and external stressful situations for the performance of the arbitration of the collective (LISEA) initially developed in basketball referees [39], and later applied in soccer referees [40]. All of this would lead to a decrease in performance efficiency, as it was demonstrated [41].…”
Section: Theorical Background and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Refereeing is one of the most challenging and laborious tasks within the field of sports (Diotaiuti et al, 2017) and a key position in sports organizations (Martínez-Moreno et al, 2021). They are responsible for managing the game well and ensuring fair play (Werger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When one tries to define SB one can find a multiplicity of definitions in this respect. Currently, most of the studies are framed within the three-dimensional approach that the syndrome is composed of emotional exhaustion, depersonalization and loss of self-fulfilment in the workplace (Martínez-Moreno et al, 2020;Pires and Ugrinowitsch, 2020;Li, et al 2018;Mikalauskas et al, 2018;Kavanagh et al, 2018;Armenta-Hernández et al, 2018;Bruschini et al, 2018;Kawamura et al, 2017;Leiter and Maslach, 2017) and in the case of students the three dimensions are: emotional exhaustion, cynicism and academic effectiveness or selfefficacy (Liu et al, 2018;Boni et al, 2018;Erschens et al, 2018;Liébana-Presa et al, 2017;Hederich-Martínez et al, 2016;Tomaschewski et al, 2014) University students, like any professional, are faced with the pressures and overloads of academic work.…”
Section: Introductionmentioning
confidence: 99%